2021
DOI: 10.1002/ecy.3565
|View full text |Cite
|
Sign up to set email alerts
|

Negative carry‐over effects on larval thermal tolerances across a natural thermal gradient

Abstract: Under climate change, marine organisms will need to tolerate or adapt to increasing temperatures to persist. The ability of populations to cope with thermal stress may be influenced by conditions experienced by parents, by both genetic changes and transgenerational phenotypic plasticity through epigenetics or maternal provisioning. In organisms with complex life cycles, larval stages are particularly vulnerable to stress. Positive parental carryover effects occur if more stressful parental environments yield m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…In this study, we used estimates of critical thermal maxima derived from laboratory experiments, which measured mosquito life history traits (including immature and adult survival and development as well as fecundity, biting rate, and egg viability) under constant temperatures, typically occurring for several hours, days, or weeks (Supplemental Table S1; summarized in Mordecai et al 2019 andVillena et al 2022). Prior work has demonstrated that the duration of heat exposure and the rate of temperature change used in heat tolerance assays, as well as the thermal history of the organism itself, including cross-generational effects, can all impact the estimated critical thermal maxima (Heerwaarden & Kellermann 2020;Kingsolver et al 2011Kingsolver et al , 2015Schiffer et al 2013;Terblanche et al 2007;Waite & Sorte 2022). As a result, there is no single definitive critical thermal maximum for a given taxon or individual, but instead a continuum depending on temporal dynamics of heat exposure and the specific trait of interest (Bates & Morley 2020;Clusella-Trullas et al 2021;Hoffmann et al 2013;Jørgensen et al 2019;Kellermann et al 2012;Lutterschmidt & Hutchison 1997).…”
Section: Discussionmentioning
confidence: 99%

How much warming can mosquito vectors tolerate?

Couper,
Desire Uwera Nalukwago,
Lyberger
et al. 2024
Preprint
“…In this study, we used estimates of critical thermal maxima derived from laboratory experiments, which measured mosquito life history traits (including immature and adult survival and development as well as fecundity, biting rate, and egg viability) under constant temperatures, typically occurring for several hours, days, or weeks (Supplemental Table S1; summarized in Mordecai et al 2019 andVillena et al 2022). Prior work has demonstrated that the duration of heat exposure and the rate of temperature change used in heat tolerance assays, as well as the thermal history of the organism itself, including cross-generational effects, can all impact the estimated critical thermal maxima (Heerwaarden & Kellermann 2020;Kingsolver et al 2011Kingsolver et al , 2015Schiffer et al 2013;Terblanche et al 2007;Waite & Sorte 2022). As a result, there is no single definitive critical thermal maximum for a given taxon or individual, but instead a continuum depending on temporal dynamics of heat exposure and the specific trait of interest (Bates & Morley 2020;Clusella-Trullas et al 2021;Hoffmann et al 2013;Jørgensen et al 2019;Kellermann et al 2012;Lutterschmidt & Hutchison 1997).…”
Section: Discussionmentioning
confidence: 99%

How much warming can mosquito vectors tolerate?

Couper,
Desire Uwera Nalukwago,
Lyberger
et al. 2024
Preprint
“…Future work should therefore assess acclimation to more extreme temperatures than studied here, to find the range at which it can no longer prevent the accumulation of damage and homeostasis is disrupted to the point of mortality (Ørsted, Jørgensen & Overgaard 2022). Another key step will be to assess potential trade-offs, for example, between parents’ investment in their own defenses against warming versus those of offspring (Waite & Sorte 2022). Nevertheless, our results imply that gradual warming may benefit ectotherms not yet living at their thermal limits if acclimation induces thermodynamic effects that enhance survival, or prove detrimental if survival declines because mechanisms of temperature compensation are disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…However, assessing responses to fluctuating temperatures, in addition to more extreme temperatures, would deliver more realistic insights into the limits beyond which acclimation no longer prevents death by heat (Ørsted et al, 2022). Another key step would be to assess trade‐offs between parents' investments in their own defences against warming versus those of offspring (Waite & Sorte, 2022). Nevertheless, our results imply that warming may unexpectedly benefit ectotherms not yet living at their thermal limits if acclimation induces thermodynamic effects that enhance survival.…”
Section: Discussionmentioning
confidence: 99%